Pipelines 2018. proceedings of sessions of the Pipelines 2018 Conference, July 15-18, 2018, Toronto, Ontario, Canada - Macey, Christopher C.; Lueke, Jason, S. (Online access: American Society of Civil Engineers (ASCE) American Society of Civil Engineers (ASCE) Conference Proceedings., 2018)
"This collection contains 38 peer-review papers on utility engineering, surveying and multidisciplinatry topics. Topics include: project management; sustainability; asset management and inspection; operations and management; and international case studies."--